2012
DOI: 10.1016/j.ypmed.2012.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Associations of physical activity with neighborhood environments and transportation modes in older Japanese adults

Abstract: Objective: We investigated associations of walking and other leisure-time physical activity (LTPA) with environmental characteristics and transportation modes in older Japanese adults. Methods:This cross-sectional study in 2010-2011 used data from 421 community-dwelling older adults aged 65-85 years living in Kasama City, rural Japan. We used the Physical Activity Scale for the Elderly to assess walking and other LTPAs, and the International Physical Activity Questionnaire Environment Module for neighborhood e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
50
7
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 24 publications
(28 reference statements)
6
50
7
3
Order By: Relevance
“…This interesting finding provides new insights. It is distinctly different from the findings of research carried out in North America, Europe and Australia, which explore those relationships between environments and physical activity participation in different urban designs and cultures …”
Section: Discussioncontrasting
confidence: 75%
“…This interesting finding provides new insights. It is distinctly different from the findings of research carried out in North America, Europe and Australia, which explore those relationships between environments and physical activity participation in different urban designs and cultures …”
Section: Discussioncontrasting
confidence: 75%
“…We mailed invitation letters to 3000 people aged 65-85 years (1200 individuals in 2009, 900 individuals each in 2010 and 2011) randomly drawn from the Basic Resident Register. 19 A total of 570 people participated in the study carried out in the Health Center in Kasama City. People aged 86 years and over were excluded from the study, as the longevity of people's 17 physical functions might be strongly affected by genetics.…”
Section: Participants and Data Collectionmentioning
confidence: 99%
“…Updating this literature review in Feb 2015, SB identified a small number of newer studies, corroborating the effect of the neighbourhood environment on walking for transport (Van Cauwenberg et al, 2014;Jia et al, 2014); of traffic on travel behaviour Tsunoda et al, 2012); and that transport problems can cause psychological distress (Taylor et al, 2012).…”
Section: Community Severance and Social Networkmentioning
confidence: 89%